Astrologic: The Effectiveness of Priming Using Chinese Zodiac Characteristics on Logical Thinking Ability - Sutikno, Sofia Paramita; Natalya, Lina; Siaputra, Ide Bagus (Universitas Ahmad Dahlan, 2025)
This experimental study examined whether Chinese zodiac personality descriptions, when used as priming stimuli, affect logical thinking ability among Generation Z students. A 2x2 factorial design (valence x validity) was applied to 105 college students aged 18-25, who were randomly assigned to one of four groups: positive-valid, positive-invalid, negative-valid, or negative-invalid. Logical thinking was measured using 15-minute Sudoku Logical Task administered before and after priming. A one-way ANOVA showed no significant overall effect of priming on logical thinking ability (F = 1.290, p-value = 0.282 > 0.05). However, paired sample t-tests revealed a significant improvement in the negative-valid (t = 3.266, p-value = 0.003 < 0.05) and negative-invalid (t = 2.495, p-value = 0.020) groups, whereas no significant changes were observed in the positive conditions. These exploratory results were based on uncorrected p-values and should be interpreted with caution due to potential Type I error inflation. These results suggest that negative descriptions, even when perceived as valid or invalid, may elicit compensatory motivation to protect one’s self-concept. The findings extend the Situated Inference Model and Self-Enhancement Theory by emphasizing affective valence as a stronger determinant of cognitive engagement than perceived validity. Practically, challenge-based feedback may enhance logical thinking when framed constructively.